Local Wisdom of Kampunglaut Community Facing Flood Disaster Rob - Ana Andriani; Beny Wijarnako; Wakhudin Wakhudin; Agung Nugroho (Proceedings Series on Social Sciences & Humanities, 2023)
The existence of the community cannot be separated from the natural environment, where they have lived for generations. Through a long process of adaptation to the natural environment, people really understand their ecological environment, so they treat their ecological environment intelligently. The universe is not only a source of exploitation, but as a common house that is continuously protected, cared for and arranged. The natural environment they live in is sometimes considered to be unusual and dangerous, but in reality, these communities do not feel worried because they live modestly with their natural environment. Ecological intelligence forges humans to organize their emotions, thoughts and actions in responding to the universe. Ecological intelligence is expressed in the form of real attitudes and behaviors that take into account ecological capacities, and give birth to a wise human attitude towards nature. Basically, case study research focuses attention on one particular object that is appointed as a case to be studied in depth so that it is able to uncover the reality behind the phenomenon. As is the case in the traditional wisdom of the people of Ujunggagak Village, Kampunglaut District, Cilacap Regency, Central Java which is formed from many activities, components or units that are interrelated and form certain functions. The case study method in this research is very appropriate to be able to uncover the mistigation of tidal flooding in Ujunggagak Village. The focus of case studies is the specification of cases in an event, including individuals, cultural groups or portraits of life, so that they can reveal forms of local wisdom that have the value of tidal flood disaster mitigation and freshwater crises.